Group differences between countries and between languages in pain-related beliefs, coping, and catastrophizing in chronic pain: A systematic review - Sharma, Saurab (2020)
To evaluate the extent to which pain-related beliefs, appraisals, coping, and catastrophizing differ between countries, language groups, and country economy.